PENGELOLAAN PEMBELAJARAN BAHASA INGGRIS DI BIDANG READING COMPREHENSION SKILL - Agusmiati Agusmiati; Zakaria Zakaria; Osa Juarsa (Manajer Pendididikan, 2017)
The purpose of the research is to describe about the management of English teaching-learning  in reading comprehension skill at the  Junior High School number 15 of  South Bengkulu. The research used qualitative descriptive method. The subjects of this research were principals, vice principals, English Teacher and students at the Junior High School Number 15 of South Bengkulu. The techniques of the collecting data were observation, interview, and documentation study. The results of the study show that: planning was planned successfully, implementation was done appropriate with the planning, evaluation was done continually, the follow up in the  English Teaching-Learning Management  in Reading Comprehension Skill was done well at the Junior High School Number 15 South Bengkulu.